The U.S. In Syrian Conflict - Alfiani Safitri (Universitas Pendidikan Indonesia (UPI), 2015)
This present research examines the representation of the United States in Syrian conflict as evidenced in the BBC International and the BBC Indonesia articles by using van Dijk’ssociocognition framework (2009a 2009b). This research employed qualitative method to describe the representation and its significance. Drawing on 10 online articles from the BBC International and the BBC Indonesia, it was found that the U.S. is represented as the Globo-cop who controls the plot in Syrian conflict. The representation is indicated by three indicators, namely: the U.S. is a firm and powerful country, the U.S. is intimate with the Opposition, and the U.S. is the Opposition group helper. In addition, through sociocognition and context analyses, it was revealed that the ideology of the BBC International and BBC Indonesia is shaped by the culture of their owners. However, the different level of representation of the U.S in the two news corporations is influenced by their target readers.Keywords: Critical Discourse Analysis, Sociocognition, Van Dijk, Representation, Translation Media, Syrian Conflict.Keywords: Critical Discourse Analysis, Sociocognition, Van Dijk, Representation, Translation Media, Syrian Conflict.